Kualitas Produk dan Harga Mempengaruhi Konsumen Dalam Memasang Jaringan Gas Rumah Tangga Di Kelurahan Wonosari Kecamatan Prabumulih Utara Kota Prabumulih - Suparni, Sri (Management Studies and Entrepreneurship Journal (MSEJ), 2021)
The development of gas distribution networks for households is one of the national priority programs aimed at energy diversification, reducing subsidies, providing clean and cheap energy as well as a complementary program for the conversion of kerosene to Liquefied Petroleum Gas (LPG) to accelerate the reduction of petroleum use. Through this program, people are expected to get cleaner, safer, and cheaper fuel. With the realization of the household gas network in Prabumulih City, the community can use the household gas network. The success of the natural gas network program for households cannot be separated from the hard work of the City Government to socialize the household natural gas network. To solve the main problems faced by the company, a descriptive analysis method is used. Total customer population 2443 customers. Then the sample obtained using the formula is 340. Based on the results obtained, it can be seen that product quality and price have a positive and significant effect on the consumer's decision to install a gas network in Wonosari Village, Prabumulih Utara District, Prabumulih City, Prabumulih City, this can be seen from the value of F count which can be F counted 386,255> F table 3.04 with a significance value (sig) of 0,000, much smaller than 0.05, then the hypothesis H3 in this study is proven, accepted. Keywords: Product Quality, Price and Consumer Decisions